A resting-state functional magnetic resonance imaging study of altered functional brain activity in cardiac arrest survivors with good neurological outcome - Wu, Qian; Wang, Gan-Nan; Hu, Hao; Chen, Xu-Feng; Xu, Xiao-Quan; Zhang, Jin-Song; Wu, Fei-Yun (Frontiers in Neurology, 2023)
Purpose: To investigate the spontaneous brain activity alterations in good outcome survivors of cardiac arrest (CA) using resting-state functional magnetic resonance imaging (rs-fMRI) with amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) methods. Material and Methods: A total of 13 CA survivors with favorable neurological outcome and 13 healthy controls (HCs) were recruited and underwent rs-fMRI scans. The ALFF and ReHo methods were applied to assess the regional intensity and synchronization of spontaneous brain activity. Correlation analyses were performed to explore the relationships between the mean ALFF and ReHo values in significant clusters and clinical parameters. Results: The survivors of CA showed significantly decreased ALFF values in left postcentral gyrus and precentral gyrus, while increased ALFF values in left hippocampus and parahippocampal gyrus than HCs. Besides, significantly decreased ReHo values were observed in left inferior occipital gyrus and middle occipital gyrus in the patients. Mean ALFF values in left hippocampus and parahippocampal gyrus were positively correlated with time to return of spontaneous circulation (r = 0.794, P = 0.006), while negatively correlated with Montreal Cognitive Assessment scores (r = -0.645, P = 0.044) in the patient group. Conclusion: Functional activity alterations in the brain areas corresponding to known cognitive and physical impairments were observed in CA survivors with preserved neurological function. Our results could advance the understanding of the neurological mechanisms underlying the residual deficits in those patients.